2020
DOI: 10.1177/0022022120972183
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Dehumanization and Emotional Labor: A Cross-Cultural Comparison Between Vietnam and the United Kingdom

Abstract: This study examined cross-cultural differences in the relationships between organizational dehumanization and both job satisfaction and turnover intentions through emotional labor (i.e., surface acting). In particular, we expected that power distance, that is, a critical value usually discussed as part of the national culture, would mitigate the deleterious effects of both organizational dehumanization and surface acting on job satisfaction and turnover intentions. Data were collected from employees in two cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…Recently, researchers have integrated these two literature more closely by examining how employees’ use of emotional labor is shaped by a mistreatment perpetrated by the organization, namely organizational dehumanization (Nguyen et al, 2021; Nguyen & Stinglhamber, 2020, 2021). Readers may recall those newspaper articles a few years ago about employees who made the uncomfortable decision to wear adult diapers to work to avoid having to ask to leave the line and risk being punished.…”
Section: An Understanding Of Interpersonal Mistreatment In the Emotio...mentioning
confidence: 99%
“…Recently, researchers have integrated these two literature more closely by examining how employees’ use of emotional labor is shaped by a mistreatment perpetrated by the organization, namely organizational dehumanization (Nguyen et al, 2021; Nguyen & Stinglhamber, 2020, 2021). Readers may recall those newspaper articles a few years ago about employees who made the uncomfortable decision to wear adult diapers to work to avoid having to ask to leave the line and risk being punished.…”
Section: An Understanding Of Interpersonal Mistreatment In the Emotio...mentioning
confidence: 99%
“…Particularly, mistreatment stemming from customers, patients, coworkers, and supervisors leads employees to engage in emotional labor to cope with the abuse situation (e.g., Adams & Webster, 2013). Recently, authors have found that mistreatment from the organization—through the concept of organizational dehumanization—may also entail emotional labor (Nguyen, Dao, et al, 2021). Organizational dehumanization, which refers to “an experience resulting from global perceptions and beliefs regarding the extent to which the abstract and distal entity that is the organization considers him/her as a tool or instrument” (Nguyen & Stinglhamber, 2021, p. 833), is an emotion-provoking experience that, as such, might lead to emotional labor in the same way as interpersonal mistreatment (Grandey, 2000).…”
Section: Latent Profiles Of Emotional Labormentioning
confidence: 99%
“…Previously some researchers found that an organization can be a source of abuse, hindrance, obstruction, or harm to its employees ( Gibney et al, 2009 ). For example, work overload, lack of organizational support, workplace bullying, lower social support from bosses and peers ( Agarwal et al, 2021 ; Nguyen et al, 2021 ). The dark side of employee behaviors has emerged as the gravest issue in organizations, depleting employee psychological resources ( Irshad and Bashir, 2020 ; Yao et al, 2020 ; Pereira and Mohiya, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…One concept that has recently emerged as destructive for both employees and organizations is organizational dehumanization. Organizational dehumanization refers to the perception of employees about organizational mistreatment as a result of their experience with the organization by treating them like machines rather than humans, having less concern for their respects, and handling them as a means to achieve organizational objectives with less capacity for willingness and sentiments ( Caesens and Stinglhamber, 2019 ; Nguyen et al, 2021 ; Sainz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%